Metasurface Beam Splitter: Broadband Terahertz Circular‐Polarization Beam Splitter (Advanced Optical Materials 3/2018). Issue 3 (5th February 2018) - Lee, Wendy S. L.; Nirantar, Shruti; Headland, Daniel; Bhaskaran, Madhu; Sriram, Sharath; Fumeaux, Christophe; Withayachumnankul, Withawat
Abstract : A terahertz metasurface consisting of metallic coaxial disk‐ring resonators is demonstrated by Wendy S. L. Lee et al. in article number1700852 . This metasurface is capable of deflecting normally incident left and right handed circularly polarized waves into opposite directions. Furthermore, this beam splitting capability is preserved over a broadband range and is highly efficient. Potential applications include polarization multiplexing in terahertz communications and analyzing the response of chiral molecules.